Detection of genetic alterations by immunoFISH analysis of whole cells extracted from routine biopsy material. - Mattsson, G; Tan, S; Ferguson, D; Erber, W; Turner, S; Marafioti, T; Mason, D (2007)
The detection of genetic abnormalities (eg, translocations, amplifications) in paraffin-embedded samples by the fluorescence in situ hybridization (FISH) technique is usually performed on tissue sections. FISH analysis of nuclei extracted from paraffin-embedded samples is also possible, but the technique is not widely used, principally because of the extra labor involved and the loss of information on tissue architecture. In this article, we report that nuclei extracted from paraffin-embedded tissue often retain at least part of the surrounding cytoplasm. Consequently, immunocytochemical labeling for a range of cellular markers (eg, of lineage or proliferation) can be performed in combination with FISH labeling, allowing specific cell populations to be analyzed for genetic abnormalities. These cell preparations are largely free of the problems associated with tissue sections (eg, truncation artifact, signals in different focal planes) so that interpretation is easy and numerical chromosomal abnormalities are readily assessed. Cells isolated from paraffin sections can be stored in suspension so that arrays can be created as and when needed from a range of neoplasms for investigation by the immunoFISH technique (for example, for studying a new genetic abnormality). This procedure represents a novel methodology, which in some settings offers clear advantages over analysis of tissue sections.